Forme di vita e relazione educativa - Segreto, Viviana (Studi sulla Formazione/Open Journal of Education, 2015)
The aim of this paper is to show that the main object of pedagogical research is relationship among people who share the same context. The analysis follows a linguistic approach, from a theoretical and metaphysical kind of language to a language of forms of life. After the linguistic turn, particularly in Ludwig Wittgenstein, forsaking a Platonic language means throwing language in forms of life, and blending it with people and their lives. So an educational process has to leave the unique, traditional pattern to open itself to different voices of life.